Relationship between athlete’s men cortisol with leukocytosis and Neutrophils numbers after exercise in cold, warm and normal temperatures conditions - Abbas Ali Gaeini; Sirous Choobineh; Sadegh Satarifard (Journal of Advanced Biomedical Sciences, 2011)
Background & Objective: Exercise and extreme environments, causes hormonal and immune systems changes. Therefore, the purpose of this study was evaluating the relationship between cortisol and leukocytosis and Neutrophil numbers after exercise in cold, warm and natural temperatures. Materials & Methods: Ten young male athletes ran on a treadmill for an hour at the intensity of %60VO2max in three temperature conditions of normal (22±1˚c, 50±5RH), cold (3±1˚c, 50±2RH) and warm (35±1˚c, 50±5RH). Blood samples were collected before and immediately after exercise. The total numbers of leukocytes and neutrophils were computed using Sysmex Kohden Nihon and serum cortisol concentrations determined by using ELISA. For comparing of data before and after exercise used from Paired T-test and for examine the relationship between variables used from Pearson Correlation Coefficient test. Results: The total leukocytes and the cortisol levels increased significantly after the exercise, in all the conditions (p<0.0001). Also, the number of neutrophils increased significantly after exercise in cold (p=0.001) and normal (p=0.001) environments. In addition, a significant relation was observed between cortisol levels and leukocytosis (R=0.783, P=0.007 and R=0.813, P=0.004) and between cortisol and Neutrophils after exercising in the natural and warm environment (R=0.806, P=0.005 and R=0.852, P=0.002). But, there was no significant relationship between these values after exercise in cold (R=0.63, P=0.051 and R=0.554, P=0.096). Conclusion: Exercise in all the three conditions causes the release of cortisol through stimulating the hypothalamic-pituitary- adrenal (HPA) and effect of cortisol receptor on immune cells could cause increase Neutrophils and leukocytosis. It seems that elevation of cortisol concentration during exercise in warm and natural environments is responsible for increase Neutrophils and leukocytosis. Moreover, during exercise in cold environments, factors other than cortisol, such as catecholamine and cardiovascular changes and muscle damage may lead to this event.